ORAL INTERPRETATION MECHANISM IN SOCIAL MEDIA: ANALYSIS OF USTAZ ADI HIDAYAT’S SIGNIFICANT RHETORIC IN YOUTUBE CHANNEL ADI HIDAYAT OFFICIAL - Ghozali, Mahbub (MUSHAF: Jurnal Tafsir Berwawasan Keindonesiaan, 2022)
The popularity of social media as a means of spreading meaningful content through lectures explaining the contents of the Qur’an has an impact on introducing new interpretation mechanisms that are carried out orally. Adi Hidayat consistently uploads lecture results containing interpretations of the Koran through the Adi Hidayat Official YouTube Channel. This study aims to find out the meaning mechanism used by Adi Hidayat by using qualitative methods with content analysis as a tool for analyzing data. The data in this study are limited to uploaded videos containing interpretations. This study found that the mechanism for conveying meaning by Adi Hidayat was not based on reading the commentary text but on an explanation mechanism that relied on memory for the meanings understood. The process of conveying the meaning of the Qur’an was chosen based on observing the audience using intonation and style that reinforces the message content of the verse. This method can be seen in the argument search process as an initial step to attract the audience’s attention to the meaning to be conveyed. This initial stage influences Hidayat’s style and intonation in emphasizing the main messages contained in each interpreted verse. Changes in meaning mechanisms that are more flexible in oral interpretation develop a systematic interpretation that can be applied in the same effort to interpret the Qur’an orally